The Effect of E-Word of Mouth on Purchase Decisions on Hilal Herbal - Putri, Rissa Meldani; Koeswandi, Tika Annisa Lestari; Rachmani, Nizza Nadya (A Social Science and Entrepreneurship Journal, 2023)
The purpose of this research was to confirm the effect of e-word of mouth on purchase decisions on herbal hilal honey. The approach in this study is a quantitative approach, the data source used is primary data obtained directly from respondents via google form, secondary data is information from research objects and literature studies as well as various journals and research reports related to the research topic. The results of this study are E-Word of Mouth has a positive and significant effect on Purchase Decisions on Herbal Hilal Honey.